Event Study: This study Do politically affiliated groups affect stock returns during the presidential Election? - Pudi Setiyawan; Lela Nurlaela Wati; Mukti Soma; Eko Kusnadi (Applied Quantitative Analysis, 2025)
This study analyzes the effect of the 2024 general election on the stock prices of companies affiliated with presidential and vice presidential candidate pairs in Indonesia. The methodology used in this study is an event study to measure abnormal returns before and after an election. The sample includes companies listed on the IDX, with as many as 34 companies listed based on connection politics. The research period comprises 40 estimation periods and 20 event periods. The statistical tools used for hypothesis testing were the t-test, paired sample t-test, and Wilcoxon signed-rank test. This study found that election-related information does not significantly impact average abnormal returns (AAR) before and after. However, the event study results show that political connections between companies with presidential and vice presidential candidates affect market reactions to new information during the event period. This study is essential for investors and capital market practitioners when formulating investment decision-making strategies during the general election period. These results are expected to serve as a reference for further studies on the influence of politics on the capital market in Indonesia.